Electronic structure manipulation via composition tuning for the development of highly conductive and acid-stable oxides. Issue 43 (21st October 2022) - Byeon, Young-Woon; Mailoa, Jonathan; Kornbluth, Mordechai; Lee, Gi-Hyeok; Cai, Zijian; Sun, Yingzhi; Yang, Wanli; Johnston, Christina; Christensen, Jake; Kim, Soo; Cheng, Lei; Kim, Haegyeom
Abstract : Our combined computations and experiments suggest the Mg-Ti-O chemical spaces for novel ternary oxide compounds that can offer high conductivity and corrosion stability to be used in fuel cell applications. Abstract : Exploring materials that simultaneously possess high conductivity and electrochemical stability is critical for various energy-conversion applications. In this study, our combined computations and experiments suggest the Mg–Ti–O chemical space for novel ternary oxide compounds offering high electrical conductivity and corrosion stability in acidic conditions to be potentially used as catalyst supporter of polymer electrolyte membrane fuel cells. High electrical conductivity (6.09 × 10 −1 S cm −1 ) is achieved at room temperature by tuning the chemical composition of Mg1− x Ti2+ x O5 while still maintaining good corrosion stability (1.2 × 10 −4 mA cm −2 after six days) in acidic conditions. Furthermore, we discover that a reducing gas environment during the synthesis increases the Ti solubility in Mg1− x Ti2+ x O5 with a reduced valence state of Ti, thus resulting in high conductivity.